Constitution-making in transition: a comparative study of the 2012 Egyptian and 2014 Tunisian constitutions - Saleh, Mona Ahmed (AUC Knowledge Fountain, 2015)
This master's project examines constitution-making in transition by analyzing both the 2012 Egyptian and the 2014 Tunisian constitutions as case studies. The processes of the two constitutions took place in quite similar post-uprising contexts in which Islamists were the majority and yet resulted in different outcomes. The project aims to identify and analyze the variables that influenced constitution-making processes in both countries and hence the outcomes as indicated in the analysis of a selected number of civil and political rights in both constitutions. The project answers three questions: Why did Islamists in Egypt gain a qualified majority at the constituent assembly, while Ennahda Islamists in Tunisia gained only a simple majority? How did these majorities impact the constitution-making process in each country, and how did the process shape the constitutional outcome? The conceptual framework of the project sets a number of factors (independent variables) that were at stake during transition and influenced the constitution-making process (intermediate variable), which, in turn, shaped the outcome (dependent variable). The project concludes that the selected articles of civil and political rights in the Tunisian constitution come closer to the international norms of the ICCPR as an attempt at reaching a compromise with the vision of the non-Islamist groups, whereas the articles in the 2012 Egyptian constitution drifted from the ICCPR, and the vision/agenda of the Islamist majority was predominant in the constitutional text. The project presents conclusions and lessons learned that could provide directions for future research on constitution-making.